On the island biogeography of aliens: a global analysis of the richness of plant and bird species on oceanic islands. Issue 7 (25th June 2015) - Blackburn, Tim M.; Delean, Steven; Pyšek, Petr; Cassey, Phillip
Abstract: Aim: (1) To characterize the relationship(s) between species richness and area for alien plant and bird species on islands, and to identify commonalities and differences in those relationships for these different taxa, and between alien and native species; (2) to test whether area per se, native species richness or human factors related to area is the primary determinant of alien species richness; and (3) to explore the effects on alien island biogeography of isolation, productivity and the time since first European landfall. Location: Islands around the world. Methods: We used structural equation models (SEMs; supported by generalized linear models) to interrogate data on the alien and native species richness of birds and plants on islands. Results: Alien plant and bird species richness were both strongly correlated with island area, with similar slopes on logarithmic axes. SEMs for both plants and birds revealed positive direct effects of native species richness and human population size, and positive indirect effects of area, on alien species richness. The models also identified indirect effects of temperature (positive) and isolation (negative) on alien species richness. Native plant and bird species richness were both predicted by direct effects of area (positive), temperature (positive) and isolation (negative). However, native plant richness was the only direct predictor of native bird species richness, and the strongest direct predictor of alien bird species richness, for islands with both plant and bird richness data. Main conclusions: Our analyses recover the species–area, species–isolation and productivity relationships in native richness. Alien species richness was most strongly related to native species richness, with additional effects of human population size. Human population size most likely determines the number of alien species that arrive on an island, while the effect of native species richness may be driven by the influence of habitat heterogeneity on the likelihood that those populations persist (establishment success).